Prognostic Value of MUC2 Expression in Colorectal Cancer: A Systematic Review and Meta-Analysis. (5th June 2018) - Li, Chao; Zuo, Didi; Yin, Libin; Lin, Yuyang; Li, Chenguang; Liu, Tao; Wang, Lei
Abstract : Background . The reliability of MUC2 as a prognostic marker in colorectal cancer (CRC) is controversial. This study evaluated the association between MUC2 expression levels in CRC tissues and prognosis. Methods . The PubMed, Web of Science, Embase, Cochrane Library, China Biology Medicine disc (CBMdisc), Wanfang Database, and China National Knowledge Infrastructure (CNKI) databases were searched to identify studies exploring the relationship between MUC2 expression in CRC tissues and overall survival (OS). Pooled hazard ratios (HRs) and risk ratios (RRs) with 95% confidence intervals (CIs) were used to evaluate the associations between MUC2 expression levels and prognosis and MUC2 expression levels and CRC clinicopathological characteristics, respectively. Results . The meta-analysis included 11 studies (2619 patients). Low MUC2 expression level was significantly associated with poor OS (HR, 1.67; 95% CI, 1.43–1.94; P < 0.00001 ) and disease-free survival (DFS)/recurrence-free survival (RFS) (HR, 1.60; 95% CI, 1.21–2.12; P = 0.001 ) in patients with CRC. Low MUC2 expression level was associated with advanced TNM stage (RR, 1.42; 95% CI, 1.26–1.60; P < 0.00001 ), lymph node metastasis (RR, 1.41; 95% CI, 1.25–1.60; P < 0.00001 ), lymphatic invasion (RR, 1.64; 95% CI, 1.26–2.12; P = 0.0002 ), rectal tumor site (RR, 1.26; 95% CI, 1.09–1.46; P = 0.001 ), and large tumor size (RR, 1.32; 95% CI, 1.02–1.70; P = 0.03 ). There were no associations between low MUC2 expression level and gender, histological grade, depth of invasion, and distant metastasis. Conclusion . The low levels of MUC2 in CRC tissues are poor prognostic factor independent of stage or other well-recognized markers of later-stage disease. Large well-designed cohort studies are required to validate MUC2 as a biomarker for poor prognosis in CRC.